2011
DOI: 10.1088/1742-6596/305/1/012027
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic model to predict the occurrence of skidding in wind-turbine bearings

Abstract: Abstract. Despite use of the best in current design practices, high-speed shaft (HSS) bearings, in a wind-turbine gearbox, continue to exhibit a high rate of premature failure. As HSS bearings operate under low loads and high speeds, these bearings are prone to skidding. However, most of the existing methods for analyzing skidding are quasi-static in nature and cannot be used to study dynamic operating conditions. This paper proposes a dynamic model, which includes gyroscopic and centrifugal effects, to study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 16 publications
1
27
0
1
Order By: Relevance
“…[17]. However, current research has shown that greater error would be found using Barus' equation for the case of large contact pressures.…”
Section: Friction Force and Moment Applied On The Ballmentioning
confidence: 73%
See 1 more Smart Citation
“…[17]. However, current research has shown that greater error would be found using Barus' equation for the case of large contact pressures.…”
Section: Friction Force and Moment Applied On The Ballmentioning
confidence: 73%
“…A study of sliding between the rollers and the races was carried out as an application of the dynamic contact model. Jain and Hunt [17] ignored the effect of centrifugal force and gyroscopic force on the contact angle of the ball, and presented a dynamic model of a high speed output shaft bearing in wind turbine transmission system. Selvaraj and Marappan [18] developed a cylindrical roller bearing test rig to measure the running speed of bearing elements at various operating condition.…”
Section: Introductionmentioning
confidence: 99%
“…LANIADO-JACOME 等 [10] 建立滚子轴承有限元接 触仿真模型,研究滚子与内外滚道之间的滑动。 JAIN 等 [11] 忽略离心力和陀螺力对接触角的影响, 建 立了风电装备高速输出轴轴承的动力学模型,研究 了滚动体的打滑特性。邵毅敏等 [12] 针对某车用深沟 球轴承,建立滚动体自转和公转两自由度动力学模 型,研究了滚动体进入载荷区所出现的咬入滑动现 象,并考虑转子加速等瞬态工况的影响规律。最近, 作者 [13] 基于 EULER 方程建立了角接触轴承时变动 力学模型,初步分析了滚动体三维空间运动行为。 尽管国内外相关学者均对轴承打滑的动力学 问题进行了一些研究工作,但研究对象局限于止推 滚动轴承(承受轴向载荷)和深沟球轴承(承受径向载 荷)。近期,刘红彬等 [14] 、贾永川和邓四二 [15] …”
Section: 润 滑 状 态 下 轴 承 的 打 滑 动 力 学 仿 真 。unclassified
“…Cui and Zheng [5] also considered this 3D motion but used a five DOF model to model a rotor-bearing system. Jain and Hunt [15] introduced a different approach; they calculated the friction forces between the balls and the races in each contact using the EHL theory. Although they did not consider the dynamics of the cage, they inserted springs of very high stiffness between the balls.…”
Section: Condition-based Maintenance Is An Extended Maintenance Appromentioning
confidence: 99%
“…The majority of the literature on dynamic models of REBs focuses on ball bearings, with single-row deep-groove ball bearings receiving the most attention. Other dynamic models are related to other configurations of single-row ball bearings, such as angular-contact ball bearings [5,15,26,42]. There are a few models for double-row ball bearings in the research literature [20,46].…”
Section: Introductionmentioning
confidence: 99%